Penggunaan Berbagai Jenis Antikoagulan Terhadap Mutu Hasil Pemeriksaan Activated Partial Thromboplastine Time (APTT) - Ellies Tunjung Sari Maulidiyanti; Fitrotin Azizah; Tri Ade Saputro; Firdausi Nuzula (Universitas Muhammadiyah Surabaya, 2022)
Activated Partial Thromboplastine Time (APTT) is a type of hemostasis examination with citrate anticoagulant 3.2% ratio 1:9. Ethylene Diamine Tetraacetic Acid (EDTA) is one of the examination materials for hematology which is often used as an anticoagulant. Apart from EDTA, other types of anticoagulants are sodium citrate and potassium oxalate. The three anticoagulants work to bind calcium ions. The purpose of this examination is to determine the use of various anticoagulants on the quality of the results of the Activated Partial Thromboplastine Time (APCT) examination. The method used in this study is an experimental study with 3 sample groups, each consisting of 9 samples in one group. The SPSS results showed a probability value of 0.000 with the Anova test, the average results of the APTT examination were administration of sodium citrate anticoagulant 25.9 seconds, potassium oxalate 70.92 seconds, and EDTA 37.5 seconds. Based on the results of these studies, there are significant differences related to the use of various anticoagulants on the quality of the results of the Activated Partial Thromboplastine Time (APTT) examination.Keywords : Activated Partial Thromboplastine Time, Antikoagulans,